Macrophages Derived From Human Induced Pluripotent Stem Cells: The Diversity of Protocols, Future Prospects, and Outstanding Questions - Lyadova, Irina; Gerasimova, Tatiana; Nenasheva, Tatiana (Frontiers in Cell and Developmental Biology, 2021)
Macrophages (Mφ) derived from induced pluripotent stem cells (iMphs) represent a novel and promising model for studying human Mφ function and differentiation and developing new therapeutic strategies based on or oriented at Mφs. iMphs have several advantages over the traditionally used human Mφ models, such as immortalized cell lines and monocyte-derived Mφs. The advantages include the possibility of obtaining genetically identical and editable cells in a potentially scalable way. Various applications of iMphs are being developed, and their number is rapidly growing. However, the protocols of iMph differentiation that are currently used vary substantially, which may lead to differences in iMph differentiation trajectories and properties. Standardization of the protocols and identification of minimum required conditions that would allow obtaining iMphs in a large-scale, inexpensive, and clinically suitable mode are needed for future iMph applications. As a first step in this direction, the current review discusses the fundamental basis for the generation of human iMphs, performs a detailed analysis of the generalities and the differences between iMph differentiation protocols currently employed, and discusses the prospects of iMph applications.